The Michigan Experience with Safety and Effectiveness of Tranexamic Acid Use in Hip and Knee Arthroplasty. (5th October 2016) - Hallstrom, Brian; Singal, Bonita; Cowen, Mark E.; Roberts, Karl C.; Hughes, Richard E.
Abstract : Background: The efficacy of tranexamic acid (TXA) in reducing blood loss and transfusion requirements in total hip and knee arthroplasty has been well established in small controlled clinical trials and meta-analyses. The purpose of the current study was to determine the risks and benefits of TXA use in routine orthopaedic surgical practice on the basis of data from a large, statewide arthroplasty registry. Methods: From April 18, 2013, to September 30, 2014, there were 23, 236 primary total knee arthroplasty cases and 11, 489 primary total hip arthroplasty cases completed and registered in the Michigan Arthroplasty Registry Collaborative Quality Initiative (MARCQI). We evaluated the association between TXA use and hemoglobin drop, transfusion, length of stay (LOS), venous thromboembolism (VTE), readmission, and cardiovascular events by fitting mixed-effects generalized linear and mixed-effects Cox models. We used inverse probability of treatment weighting to enhance causal inference. Results: For total hip arthroplasty, TXA use was associated with a smaller drop in hemoglobin (mean difference = −0.65 g/dL; 95% confidence interval [CI] = −0.60 to −0.71 g/dL), decreased odds of blood transfusion (odds ratio [OR] = 0.72; 95% CI = 0.60 to 0.86), and decreased readmissions (OR = 0.77; 95% CI = 0.64 to 0.93) compared with no TXA use. There was no effect on VTE (hazard ratio [HR] = 0.91; 95% CI = 0.62 to 1.33), LOS (incident rate ratio [IRR] = 1.00; 95% CI = 0.97 to 1.03), or cardiovascular events (OR = 0.85; 95% CI = 0.47 to 1.52). For total knee arthroplasty, TXA was associated with a smaller drop in hemoglobin (mean difference = −0.68 g/dL; 95% CI = −0.64 to −0.71 g/dL) and one-fourth the odds of blood transfusion (OR = 0.26; 95% CI = 0.21 to 0.31). There was an association with decreased risk of VTE within 90 days after surgery (HR = 0.56; 95% CI = 0.42 to 0.73), slightly decreased LOS (IRR = 0.93; 95% CI = 0.92 to 0.95), and no association with readmissions (OR = 0.90; 95% CI = 0.79 to 1.04) or cardiovascular events (OR = 1.12; 95% CI = 0.74 to 1.71). Conclusions: In routine orthopaedic surgery practice, TXA use was associated with decreased blood loss and transfusion risk for both total knee and total hip arthroplasty, without evidence of increased risk of complications. TXA use was also associated with reduced risk of readmission among total hip arthroplasty patients and reduced risk of VTE among total knee arthroplasty patients, and did not have an adverse effect on cardiovascular complications in either group. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.